2020
DOI: 10.1002/aenm.201903815
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of Single‐Atom Catalysts for Oxygen Reduction Reaction

Abstract: His thesis mainly focuses on developing graphene-based single-atom catalysts and the surface engineering of Pt-based nanostructures for energy conversion and storage. Xiangfeng Duan received his Ph.D. in physical chemistry from Harvard University and his B.S. degree in chemistry from the University of Science and Technology of China. His research group at UCLA focuses on developing new material systems for highly efficient energy harvesting, conversion, and storage via the rational design and nanoscale integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
220
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(222 citation statements)
references
References 137 publications
(235 reference statements)
2
220
0
Order By: Relevance
“…In their study, Pd SA/FeOx could be the best candidates for further applications, which even exhibited better performance than reported Pt SA/FeOx and Ni SA/FeOx. Based on the theoretical studies, further precise characterizations such as coordination number, the second-and higher-shell coordinations were mostly performed by combining experimental XAS spectra and theoretical modelings [31,53]. For example, Jaouen et al reported that the identification of Fe-SA/N4C12, Fe-SA/N4C10, and Fe-SA/N4C12Ox could be indicated by experimental XANES and related theoretical spectra [54].…”
Section: Characterization Of Coordination Environmentmentioning
confidence: 99%
“…In their study, Pd SA/FeOx could be the best candidates for further applications, which even exhibited better performance than reported Pt SA/FeOx and Ni SA/FeOx. Based on the theoretical studies, further precise characterizations such as coordination number, the second-and higher-shell coordinations were mostly performed by combining experimental XAS spectra and theoretical modelings [31,53]. For example, Jaouen et al reported that the identification of Fe-SA/N4C12, Fe-SA/N4C10, and Fe-SA/N4C12Ox could be indicated by experimental XANES and related theoretical spectra [54].…”
Section: Characterization Of Coordination Environmentmentioning
confidence: 99%
“…By pyrolysis of a bimetallic ZnCo-ZIF with a Zn/Co ratio of 10 at 900°C, Xiao et al for the first time revealed the homonuclear binary Co 2 N 5 configuration in the carbon matrix [159] electrocatalysts by in situ encapsulating Fe(acac) 2 , Fe 2 (CO) 9 , and Fe 3 (CO) 12 in the nanocavity of ZIF-8 during the synthesis of ZIF-8 followed by pyrolysis at 800°C [125]. [11,160,162], including Fe-N 2 , Fe-N 4 -C 8 , Fe-N 4 -C 10 , Fe-N 4 -C 12 , Fe-N 4 Td, Fe-N 5 , and Fe-N 6 . In most cases, single-atom Fe tended to form planar Fe-N 4 moieties by coordinating with four pyrrolic or pyridinic N atoms (Fe-N 4 -C 12 or Fe-N 4 -C 10 , respectively) after treating the Fe, N, and C precursors at high temperature (above 800°C).…”
Section: Researchmentioning
confidence: 99%
“…Due to unique empty d orbital structure, atomically dispersed Fe atoms could feature various types of coordination structures and numerous M-N x -C y SAECs have been reported [ 11 , 160 , 162 ], including Fe-N 2 , Fe-N 4 -C 8 , Fe-N 4 -C 10 , Fe-N 4 -C 12 , Fe-N 4 Td, Fe-N 5 , and Fe-N 6 . In most cases, single-atom Fe tended to form planar Fe-N 4 moieties by coordinating with four pyrrolic or pyridinic N atoms (Fe-N 4 -C 12 or Fe-N 4 -C 10 , respectively) after treating the Fe, N, and C precursors at high temperature (above 800°C).…”
Section: Saecs For Oxygen Reduction Reactionsmentioning
confidence: 99%
“…[2][3][4] These losses have been attributed to the unfavorable scaling between the binding energies of OXR intermediates, in particular *OOH vs *OH. 2,5,6 Although recent discoveries of low-cost alternatives are encouraging, 7,8 it is likely that their performance is also constrained by similar intrinsic limitations. Despite slight material-specific variations, the robustness of the *OOH vs *OH linear correlation across different materials and computational methods is well-established.…”
mentioning
confidence: 99%